Phytochemical and morpho-anatomical study of the vegetative organs of Psychotria fractistipula L.B.Sm., R.M. Klein & Delprete (Rubiaceae) - Camila Freitas de Oliveira; Vinicius Bednarczuk Oliveira; Vanessa Barbosa Bobek; Katlin Suellen Rech; Fernando Cesar Martins Betim; Josiane de Fatima Gaspari Dias; Sandra Maria Warumby Zanin; Obdulio Gomes Miguel; Marilis Dallarmi Miguel (Universidade de São Paulo, 2020)
Psychotria fractistipula L.B.Sm, R.M. Klein & Delprete (Rubiaceae) is found in the existing Atlantic Forest in the South of Brazil, in the Paraná and Santa Catarina States. The members of Rubiaceae are characterized chemically by the presence of alkaloids, some pharmacological properties of which include antifungal, antibacterial, analgesic, antioxidant, antimutagenic, and antiviral activities. In this study, we report the results of anatomical, morphological, and histochemical analyses of the leaves and stems of the Rubiaceae family member, P. fractistipula. The anatomical analysis involved of light microscopy and scanning electron microscopy. Morpho-anatomical and histochemical characterization were made using standard methodology. The isolated compounds were identified by Nuclear Magnetic Resonance spectroscopic analysis. The following structures are highlighted as the distinctive features of the species: presence of petiolate leaves and a petiole base, leaf blade with smooth cuticle on both surfaces, paracytic stomata, and, dorsiventral mesophyll and presence of trichomes on the leaves and stems. Phytosteroids, identified as β-sitosterol and campesterol, were observed in the hexane fraction of the stem. Future studies should focus on the isolation of other fractions of interest and their characterization through specific biological and cytotoxicity assays.